Expression and Characterization of Drosophila Signal Peptide Peptidase-Like (sppL), a Gene That Encodes an Intramembrane Protease - Casso, David J. (Public Library of Science, 2012)
Intramembrane proteases of the Signal Peptide Peptidase (SPP) family play important roles in developmental, metabolic and signaling pathways. Although vertebrates have one SPP and four SPP-like (SPPL) genes, we found that insect genomes encode one Spp and one SppL. Characterization of the Drosophila sppL gene revealed that the predicted SppL protein is a highly conserved structural homolog of the vertebrate SPPL3 proteases, with a predicted nine-transmembrane topology, an active site containing aspartyl residues within a transmembrane region, and a carboxy-terminal PAL domain. SppL protein localized to both the Golgi and ER. Whereas spp is an essential gene that is required during early larval stages and whereas spp loss-of-function reduced the unfolded protein response (UPR), sppL loss of function had no apparent phenotype. This was unexpected given that genetic knockdown phenotypes in other organisms suggested significant roles for Spp-related proteases.